Selection of an Effective Trajectory of Regional Socio-Economic Development - Kuklin, Aleksandr Anatolyevich; Korobkov, Ilya Vladimirovich (Economy of Regions, 2018)
Currently, the socio-economic crisis and tension in external economic environment significantly complicate the task of strategic planning of regional socio-economic development. However, this task is crucially relevant. Its solution requires a multiaspect assessment of regional socio-economic situation. This assessment should take into account the impact of numerous factors, possible “traps”. We propose to use a composite indicator “Index of the welfare of an individual and inhabited area” to assess the socio-economic situation in a region. Using the method of correlation analysis, we selected 6 key indicators: natural population growth rate, mortgage arrears, total unemployment, percentage of the population with incomes below the subsistence level, ratio of budget spending on education to the gross regional product (GRP), ratio of budget spending on healthcare to the gross regional product (GRP). The value domain of each indicator is divided on 7 crisis zones. This allows assessing the socio-economic system situation. We have substantiated the behaviour of regional socio-economic system on the example of the Ural Federal District in the period from 2000 to 2017. Furthermore, we have made projections for the period from 2018 to 2021. The dynamics of four indicators from six demonstrates reveals a post-crisis recovery. However, the direct impact on two budgetary indicators can increase the general welfare in a region. Comparing the dynamics of the index of the welfare of an individual and inhabited area with GRP shows that we can use the index of the welfare of an individual and inhabited area to forecast the dynamics GRP. The research results can be applied for developing measures to enhance the socio-economic development of regions.